IDENTIFIKASI ATRIBUT DIMENSI SOSIAL, EKONOMI, DAN LINGKUNGAN TERHADAP KEBERLANJUTAN INDUSTRI PENGGILINGAN PADI DAN BATU BATA DI KABUPATEN PRINGSEWU - Oktavia, Dian; Persada, Citra; Abidin, Zainal (Universitas Galuh, 2023)
One of the industrial sectors that has grown a lot in Lampung Province is the Small Medium Industry (IMK), there are 95,041 businesses/companies spread throughout the Lampung Province, 92,214 businesses (97.03 %) of which are micro industries and the rest are small industries. This study aims to identify the social, economic and environmental dimensions and their attributes on the sustainability of the rice and brick milling industry in Pringsewu District. The data used is primary data for 2022. The type of research used is descriptive qualitative. Based on the results of the study, it showed The economic dimension has the attributes of income, sales volume, production costs, production capacity, availability of raw materials, and availability of energy. The social dimension uses attributes, educational level, industrial business experience, the age of the respondent, the quality of human resources (education) employment, and public health. The environmental dimension uses the attributes of waste management, health, proximity to similar industrial areas, suitability for business placement (RTRW), building density (KDB), and fulfillment of complete business permits.